Structured reflection increases intentions to reduce other people's health risks during COVID-19. Issue 5 (3rd October 2022) - Ramos, Jairo; Grant, Marrissa D; Dickert, Stephan; Eom, Kimin; Flores, Alex; Jiga-Boy, Gabriela M; Kogut, Tehila; Mayorga, Marcus; Pedersen, Eric J; Pereira, Beatriz; Rubaltelli, Enrico; Sherman, David K; et al.
Abstract: People believe they should consider how their behavior might negatively impact other people, Yet their behavior often increases others' health risks. This creates challenges for managing public health crises like the COVID-19 pandemic. We examined a procedure wherein people reflect on their personal criteria regarding how their behavior impacts others' health risks. We expected structured reflection to increase people's intentions and decisions to reduce others' health risks. Structured reflection increases attention to others' health risks and the correspondence between people's personal criteria and behavioral intentions. In four experiments during COVID-19, people ( N = 12, 995) reported their personal criteria about how much specific attributes, including the impact on others' health risks, should influence their behavior. Compared with control conditions, people who engaged in structured reflection reported greater intentions to reduce business capacity (experiment 1) and avoid large social gatherings (experiments 2 and 3). They also donated more to provide vaccines to refugees (experiment 4). These effects emerged across seven countries that varied in collectivism and COVID-19 case rates (experiments 1 and 2). Structured reflection was distinct from instructions to carefully deliberate (experiment 3). Structured reflection increased the correlation between personal criteria and behavioral intentions (experiments 1 and 3). And structured reflection increased donations more among people who scored lower in cognitive reflection compared with those who scored higher in cognitive reflection (experiment 4). These findings suggest that structured reflection can effectively increase behaviors to reduce public health risks.